Сезонная и межгодовая изменчивость крупномасштабных температурных фронтов Тропической Атлантики по спутниковым данным - Скрипалева, Е.А. (Видавничий дім "Академперіодика" НАН України, 2008)
Features of the seasonal and interannual variabilities of large-scale temperature fronts in the Tropical Atlantic are investigated on the basis of sea surface temperature satellite observations during 1985–2001. The front’s climatic seasonal cycle is described. It is shown that the maximal interannual variations of characteristics are typical of the North Tropical and North Subtropical fronts and are equal to 0.35 ºС/54 km for front’s intensity, 600–700 km for the spatial displacement, and 4 ºС for front’s temperature. The significant correlation between front’s characteristics and the indices of atmospheric circulation NAO (North Atlantic Oscillation) and SOI (South Oscillation) is found.